Pengaruh Citra Merek, Inovasi Produk, Lokasi dan Cita Rasa Terhadap Keputusan Pembelian Jajanan di UD Dian Coklat Papar - Indriyana Zunitha; Baju Pramutoko; Dadang Afrianto (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
This research aims to investigate the influence of brand image (X1), product innovation (X2), location (X3), and taste (X4) variables on purchasing decisions (Y) for snacks at UD Dian Coklat Papar. This is a quantitative research study. Data collection techniques include primary data and secondary data. Sample selection was done using the accidental sampling metho, with a total 100 respondents from UD Dian Coklat Papar. Date for this research were collected through questionnaires, interviewews, and literature review. The analysis used in this study include validity test, Reliability test, classic assumption test, multiple linear regression analiysis, t-test, f0test, and coefficient of determination test. The results of the research obtained the multiple linear regression equation Y= 1.522 + 0.239X1 + 0.222X2 + 0.241X3+0.241X4 and the t-test results of the brand image variable had a partially significant effect on purchasing decisions with a sig result of 0.033 < 0.05. Product innovation has a partially significant effect on purchasing decisions, with a sig value. 0.024 > 0.05. location has a partially significant effect on purchasing decisions, with the resulting sig. 0.020 > 0.05. Taste has a partially significant effect on purchasing decisions, with a sig. 0.026 > 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that brand image, product innovation, location and taste image simultaneously and significantly influence purchasing decisions for snacks at UD Dian Coklat explained.